Vanadium(III)/Vanadium(II) and Hydrogen Evolution Thermodynamic Behavior at the Negative of the All-Vanadium Redox Flow Batteries. Issue 12 (1st January 2017) - Chen, Fuyu; Gu, Shiyan; Ma, Qingbang; Liu, Qingyu; Zhang, Min
Abstract : The major negative reaction in all vanadium redox flow batteries (VRFBs) is oxidation-reduction reaction of V 3+ /V 2+ couple, while the side reaction is hydrogen evolution reaction (HER). This work demonstrates a method to determine the reaction priority of V 3+ reduction and HER occurring at the negative graphite electrode by using steady state polarization curve. The result shows that the reaction priority of V 3+ reduction and HER has a strong influence on the state of charge(SoC), hydrogen ion activity and density of charging current. Under the constant charging current density, the method can be concluded the priority reaction occurred at the negative electrode under a given SoC and concentration of proton.